Green synthesis of magnetite (Fe3O4) nanoparticles using seaweed (Kappaphycus alvarezii) extract - Yew, Y. P. (Springer New York LLC, 2016)
In this study, a simple, rapid, and eco-friendly green method was introduced to synthesize magnetite nanoparticles (Fe3O4-NPs) successfully. Seaweed Kappaphycus alvarezii (K. alvarezii) was employed as a green reducing and stabilizing agents. The synthesized Fe3O4-NPs were characterized with X-ray diffraction (XRD), ultraviolet-visible spectroscopy (UV-Vis), Fourier transform infrared (FT-IR), and transmission electron microscopy (TEM) techniques. The X-ray diffraction planes at (220), (311), (400), (422), (511), (440), and (533) were corresponding to the standard Fe3O4 patterns, which showed the high purity and crystallinity of Fe3O4-NPs had been synthesized. Based on FT-IR analysis, two characteristic absorption peaks were observed at 556 and 423 cm−1, which proved the existence of Fe3O4 in the prepared nanoparticles. TEM image displayed the synthesized Fe3O4-NPs were mostly in spherical shape with an average size of 14.7 nm.